PERISTILAHAN TATA BOGA TRADISIONAL DALAM MASYARAKAT DAYAK KANAYATN - Krystia, Yolenta Bella; Simanjuntak, Hotma; Patriantoro, Patriantoro (Universitas Tanjungpura, 2024)
This study aims to describe the form of terminology, describe the meaning of terminology and produce a form of implementation Indonesian language learning based on traditional Dayak Kanayatn cuisine. The method used in this study is descriptive with a qualitative form. The data sources in this study were native speakers of the Kanayatn Dayak tribe and the research data were traditional food and beverages. Data collection techniques are interview techniques and direct observation techniques. This research produced 79 data on culinary terminology in the Kanayatn Dayak community consisting of 18 data on staple food terms, 7 data on beverage terms, 6 data on snack terms, 18 data on ingredients, 9 data on how to make, 9 tools. 18 and 21 general terms, 51 special terms. There are 49 data for monomorphemic terminology, 8 data for polymorphemic terms, and 22 data for phrases. The meaning contained in the traditional culinary terminology of the Dayak Kanayatn community is based on 55 data of lexical meaning, 8 data of grammatical meaning, and 5 data of cultural meaning. The form of Indonesian learning texts based on traditional culinary terminology in the Kanayatn Dayak community produces learning texts, namely procedural texts.